Studi Literatur Pengaruh Aktivitas Fisik Terhadap Osteoarthritis Lutut Lansia - Desak Kadek Sastrawati; Putu Handi Partiwi; Luh Putu Prima Widya Ridwanti; Abdul Haris; I Ketut Astawa; I Pasek Wayan Agung Susila; Ni Luh Dwi Indrayani (Dinasti Research, 2025)
Osteoarthritis is a musculoskeletal rheumatic disease that is one of the musculoskeletal disorders that is often experienced by the elderly. Aging is the biggest risk factor for OA. Symptoms of osteoarthritis include pain, swelling, stiffness and difficulty moving the affected joint. Clinical guidelines recommend physical activity as a treatment for OA sufferers with evidence-based health benefits, such as reducing pain, improving function and improving quality of life. This literature study was conducted with the aim of exploring studies related to physical activity and knee osteoarthritis in the elderly. A comprehensive search strategy was used to identify relevant articles through the EMBASE, PubMed databases covering the period 2019 to 2024. Eligible studies were selected according to the eligibility criteria based on the PICO selection criteria. The importance of physical activity in the elderly as a form of prevention against degenerative diseases and maintenance of functional capacity that can reduce the risk of knee osteoarthritis in the elderly. Excessive levels of physical activity and high intensity can worsen the development of knee osteoarthritis in the elderly. Physical activity that is carried out regularly and supervised by experts can improve the quality of life of the elderly and reduce the risk of joint pain caused by knee osteoarthritis. The results of this study indicate that there is an influence between physical activity and knee osteoarthritis in the elderly.